Pengaruh Media Edukasi Leaflet terhadap Keterampilan Ibu dalam Merawat Bayi BBLR - Dwi Astutik; Kurnia Wijayanti; Indra Tri Astuti (Pusat Riset dan Inovasi Nasional, 2025)
Proper care of LBW is crucial, as LBW infants are susceptible to illnesses such as infections, unstable body temperature, and respiratory disorders. Mothers' unpreparedness in caring for LBW infants is due to a lack of knowledge regarding infant care. Knowledge can be improved by providing interventions in the form of providing information using media, one of which is leaflets. This study aims to determine the effect of educational leaflets on mothers' skills in caring for LBW infants. This study used a quasi-experimental study with a pretest-posttest with control group design. The sample size was 38 postpartum mothers who gave birth to LBW infants, consisting of 19 mothers in the intervention group and 19 mothers in the control group obtained through purposive sampling technique. Data were collected using a questionnaire on mothers' skills in caring for LBW infants and leaflets. Data analysis was performed using the Wilcoxon test to examine the effect of educational leaflets on mothers' skills in caring for LBW infants and the Mann-Whitney test to find differences in mothers' skills in caring for LBW infants between the intervention and control groups. There is an influence of leaflet educational media on mothers' skills in caring for LBW babies at Dr. H. Soewondo Kendal Regional General Hospital p-value = 0.000 (<0.05). There is a difference in mothers' skills in caring for LBW babies between the intervention group and the control group p value (0.002), where the average value of mothers' skills between the intervention group and the control group shows a difference of 2.31. Education about LBW care through leaflet media improves parents' skills in caring for LBW at home, because leaflets provide informative visualization of knowledge as a medium that is easy to understand.